2019
DOI: 10.1186/s13052-018-0598-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatomegaly and type 1 diabetes: a clinical case of Mauriac’s syndrome

Abstract: BackgroundHepatic glycogenosis is characterized by excessive glycogen accumulation in hepatocytes and represents a complication of poor controlled type 1 diabetes. It can be caused by excessive insulin doses or recurrent ketoacidosis episodes. Mauriac’s syndrome is a rare disease, which includes short stature, growth maturation delay, dyslipidemia, moon facies, protuberant abdomen, hepatomegaly with transaminase elevation. It has become even less common after the emergence of advances on diabetes treatment, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…These render them at a high risk of complications with recurrence of DKA. Some previously reported cases of glycogenic hepatopathy also had similar socioeconomic challenges, which led to poor glycemic control (29).…”
Section: Discussionmentioning
confidence: 98%
“…These render them at a high risk of complications with recurrence of DKA. Some previously reported cases of glycogenic hepatopathy also had similar socioeconomic challenges, which led to poor glycemic control (29).…”
Section: Discussionmentioning
confidence: 98%
“…The cause of HG is due to alternating periods of hyperglycemia and hyperinsulinemia. Hyperinsulinemia resulting from insulin administration stimulates the synthesis of glycogen from excessive hepatic glucose [ 7 ]. Histological features of HG are similar to glycogen storage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Histological features of HG are similar to glycogen storage disease. These features include glycogen accumulation and glycogenated nuclei [ 7 ]. Some investigators suggested that a genetic mutation in an enzyme of glycogen metabolism combined with persistent hyperglycemia may be the cause of hepatomegaly in MS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disease responds well to adequate control of glycaemia, dietary management and adherence to therapy. 2,3 We describe our experience of this entity at our centre over the last 15 years.…”
Section: Introductionmentioning
confidence: 99%